Analysis Of Marketing Efficiency Of Spices (Case Study In Tonu Jaya Village, Huamual Belakang District, West Seram District) - Wa Ode S. Judin; M. Turukay; S.P. Palembang (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine marketing channels, marketing margins, and marketing efficiency. The samples taken were 35 farmers in Tonu Jaya Village using the snowball method. The data collected are primary and seconday data which are both quantitative and qualitative. The method used in this study is a direct interview method using a questinnaire containing a list of questions. Data analysis used is descriptive analysis, marketing margin analysis, and marketing efficiency analysis. The results showed that there was one marketing channel for ginger spice plants in Tonu Jaya Village. The total marketing margins for ginger is Rp 11.000/kg. The marketing of ginger spices in Tonu Jaya Village has been efficient.